2019
DOI: 10.3164/jcbn.18-60
|View full text |Cite
|
Sign up to set email alerts
|

Positive influence of aqua exercise and burdock extract intake on fitness factors and vascular regulation substances in elderly

Abstract: Health issues in elderly individuals are often complex and tend to lead to chronic diseases; such issues can be due to a decline in fitness resulting from lack of physical activity. Aqua exercise and burdock are positive effects on cardiovascular disease and vascular health. This study investigated the changes due to aqua exercise and burdock extract intake in senior fitness, prostaglandin I2 (PGI2), and thromboxane A2 (TXA2) in elderly women. Forty elderly women (65–80 years) volunteered for this study. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Nagai et al (29) reported that arm and trunk muscle mass in older individuals increase after a 12-week resistance-training program with maslinic acid supplementation. Ha et al (30) found that aerobic capacity in the 6-min walking test in older individuals increases after a 12-week aquatic exercise program with burdock extract supplementation. Kumagai et al (31) reported that adding higher daily physical activity levels to calorie restriction is needed in overweight and obese men for increasing circulating levels of testosterone, a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nagai et al (29) reported that arm and trunk muscle mass in older individuals increase after a 12-week resistance-training program with maslinic acid supplementation. Ha et al (30) found that aerobic capacity in the 6-min walking test in older individuals increases after a 12-week aquatic exercise program with burdock extract supplementation. Kumagai et al (31) reported that adding higher daily physical activity levels to calorie restriction is needed in overweight and obese men for increasing circulating levels of testosterone, a Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise regimens reportedly exert a significant effect on MS indicators 29 , and are considered as a valuable non-pharmacological approach to MS management. The aim of this study was to investigate the combined effects of AE and BE on body composition and serum gonadal steroid hormones, as well as their correlation in elderly women with MS. Based on our previous findings 18 , 26 , we hypothesized that the combined effects of AE and BE would lead to additive or synergistic improvement in MS-related body composition and sex hormone levels in elderly women with MS. The results indicated that both AE and BE interventions individually decreased abdominal fat and waist circumference, which induced beneficial changes in the levels of testosterone, estradiol, and SHBG.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are controversial issues regarding the effects of physical exercise on sex hormone among elderly women, several studies have revealed that estradiol, testosterone, and SHBG levels are enhanced after adopting an active and healthy lifestyle 15 – 17 . Additionally, we observed that water-based aquatic exercise (AE), an acceptable compromise between exercise effectiveness and safety intervention for the elderly, improved fitness and vascular-related factors in elderly women without MS 18 , suggesting that regular AE might also be beneficial in elderly women with MS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 17 , 18 ) Then the MCE was prepared following the method optimized for natural plants as described in the previous studies. ( 19 , 20 ) Subsequently, 4 kg of dried MCE and 6,000 ml of water was added to the extractor, and the mixture was extracted by heating at 100°C under a pressure of 0.7 kg/cm 2 for 3 h. The extracted MCE was then sealed in a small plastic bag of 100 ml and stored in a refrigerator. To analyze the basic ingredients, we commissioned the Korea Food Research Institute and Pukyong National University Food Analysis Center.…”
Section: Methodsmentioning
confidence: 99%